1998
DOI: 10.1111/j.1540-8159.1998.tb00125.x
|View full text |Cite
|
Sign up to set email alerts
|

Is the Atrial High Rate Episode Diagnostic Feature Reliahle in Detecting Paroxysmal Episodes of Atrial Tachyarrhythmias?

Abstract: The atrial high rate episode diagnostic in the Thera pacemaker reports frequency, duration, and date/time of atrial tachyarrhythmias according to programmed criteria. The aim of the study was to validate the atrial high rate episode diagnostic feature. Episodes of atrial fibrillation recorded by Holter monitoring were compared to episodes detected by the pacemaker. Forty five ambulatory (Holter) recordings were used for evaluation. Thirty of 45 ambulatory (Holter) recordings showed sinus rhythm. On 4 of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 8 publications
2
62
0
Order By: Relevance
“…963,964 These devices can also assess long-term AF burden, burden trends, and late or asymptomatic recurrences. 940,965,966 The ability to record intracardiac atrial electrograms provides excellent sensitivity and specificity for the diagnosis of atrial arrhythmias, especially with durations exceeding a few minutes.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…963,964 These devices can also assess long-term AF burden, burden trends, and late or asymptomatic recurrences. 940,965,966 The ability to record intracardiac atrial electrograms provides excellent sensitivity and specificity for the diagnosis of atrial arrhythmias, especially with durations exceeding a few minutes.…”
Section: Section 8: Follow-up Considerationsmentioning
confidence: 99%
“…They reported that stored episodes digitally classified by the pacemaker as Ͼ250 beats per minute and Ͼ5 minutes in duration had a high correlation (88%) with the tachyarrhythmia validated by simultaneous stored intracardiac electrograms. With regards to actual electrocardiographic confirmation of arrhythmia, Seidel et al 7 compared Holter monitor recordings to pacemaker diagnostic reports. They concluded that optimal programming for reliable arrhythmia detection (98% sensitivity and 100% specificity) could be attained with exactly the same programming as pacemakers were programmed in our study: detection rate 220 beats per minute, onset number of beats 10, and termination number of beats 20.…”
Section: Discussionmentioning
confidence: 99%
“…The atrial detection rate was programmed to 220 bpm so as to include only episodes of atrial fibrillation and exclude slower atrial tachycardias. 7 The onset detection number of beats was 10 and the termination number was 20 consecutive beats at a rate below the detection rate, for the purpose of excluding short episodes of atrial premature beats. Intracardiac electrograms were not recorded in order to preserve pacemaker memory to register a greater number of events.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, device-derived atrial high rate episodes correlate with true AF diagnosis. 18, 19 In one study, 38% of patients with a history of AF had episodes of AF lasting more than 48 hours noted at the time of interrogation despite these patients being asymptomatic and in sinus rhythm at the time of evaluation. 20 In patients receiving pacemakers for sinus node dysfunction up to 68% may have device-documented AF over time.…”
Section: As Submitted Tomentioning
confidence: 99%